(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article analyzes migration processes in the Middle East region, their causes and consequences, prospects for developing cooperation between the countries of the region, and the role of international and regional organizations in this regard. The article highlights the obstacles to addressing the growing migration problem and offers suggestions on how to address them. In addition, the specificity of the approaches to migration, the similarities, and differences in the research conducted by scientists are covered in detail. The complexities of the migration process, the diversity of factors that lead to migration, and other important issues are also described. It is well known that the problem of migration is global in nature and many people are leaving their homes and families in search of a better life and income. However, in addition to the obvious economic benefits, migration also has other serious consequences. Serious problems that are likely to occur through this article have also been predicted, all proven by facts. In turn, the relevance of the approaches put forward in the article is also interpreted in terms of the functions they have been assigned based on the current state of the migration process.